Influence of Toxoplasma gondii acute infection on cholinesterase activities of Wistar rats - Tonin A.A. (2013)
Several studies have shown the mechanisms and importance of immune responses against Toxoplasma gondii infection and the notable role of cholinesterases in inflammatory reactions. However, the association between those factors has not yet been investigated. Therefore, the aim of this study was to evaluate the acetylcholinesterase (AChE) activity in blood and lymphocytes and the activity of butyrylcholinesterase (BChE) in serum of rats experimentally infected with T. gondii during the acute phase of infection. For that, an in vivo study was performed with evaluations of AChE and BChE activities on days 5 and 10 post-infection (PI). The activity of AChE in blood was increased on day 5 PI, while in lymphocytes its activity was enhanced on days 5 and 10 PI (P<0.05). No significant difference was observed between groups regarding to the activity of BChE in serum. A positive (P<0.01) correlation was observed between AChE activity and number of lymphocytes. The role of AChE as an inflammatory marker is well known in different pathologies; thus, our results lead to the hypothesis that AChE has an important role in modulation of early immune responses against T. gondii infection. © 2013, Korean Society for Parasitology and Tropical Medicine.